IMPLEMENTASI SRIKANDI PADA BAGIAN UMUM SEKRETARIAT DAERAH KABUPATEN JOMBANG - Yudi, Amanda Salsabilah Syah; Pertiwi, Vidya Imanuari (Jurnal Progress Administrasi Publik, 2024)
Jombang Regency is one of the regencies in East Java Province which is also committed to accelerating digitalization. SPBE has been made a regional development priority for Jombang Regency in 2022 as stated in Jombang Regency Regional Regulation Number 08 of 2021 concerning Amendments to Regional Regulation Number 1 of 2019 concerning the Regional Medium Term Development Plan (RPJMD) of Jombang Regency for 2018-2023 which includes the objectives of achieving SPBE index until 2023 with a very good target. On this basis, the General Section of the Jombang Regional Secretariat as one of the OPDs within the Jombang Regency Government is realizing SPBE in carrying out government administration services in the field of correspondence and archives through the SRIKANDI Application. This research was conducted to find out how SRIKANDI is implemented in the General Section of the Jombang Regency Regional Secretariat. This application will be implemented in 2022 to make it easier to create and distribute letters and archives electronically. The method in this research is descriptive qualitative with data collection techniques through interviews, observation, literature and bibliography, and documentation. Informants were taken using the purposive sampling method. The focus of this research consists of four aspects: 1) Communication; 2) Resources; 3) Disposition; 4) Bureaucratic Structure. The research results show that the implementation of SRIKANDI in the General Section as a whole can be said to be successful even though there are obstacles both internal and external that need to be corrected so that its use can be maximized. Keywords : Implementation, Public Service, SPBE, Archieve